Cytokine therapy‐mediated neuroprotection in a Friedreich's ataxia mouse model. Issue 2 (23rd February 2017) - Kemp, Kevin C.; Cerminara, Nadia; Hares, Kelly; Redondo, Juliana; Cook, Amelia J.; Haynes, Harry R.; Burton, Bronwen R.; Pook, Mark; Apps, Richard; Scolding, Neil J.; Wilkins, Alastair
Abstract : Objectives: Friedreich's ataxia is a devastating neurological disease currently lacking any proven treatment. We studied the neuroprotective effects of the cytokines, granulocyte‐colony stimulating factor (G‐CSF) and stem cell factor (SCF) in a humanized murine model of Friedreich's ataxia. Methods: Mice received monthly subcutaneous infusions of cytokines while also being assessed at monthly time points using an extensive range of behavioral motor performance tests. After 6 months of treatment, neurophysiological evaluation of both sensory and motor nerve conduction was performed. Subsequently, mice were sacrificed for messenger RNA, protein, and histological analysis of the dorsal root ganglia, spinal cord, and cerebellum. Results: Cytokine administration resulted in significant reversal of biochemical, neuropathological, neurophysiological, and behavioural deficits associated with Friedreich's ataxia. Both G‐CSF and SCF had pronounced effects on frataxin levels (the primary molecular defect in the pathogenesis of the disease) and a regulators of frataxin expression. Sustained improvements in motor coordination and locomotor activity were observed, even after onset of neurological symptoms. Treatment also restored the duration of sensory nerve compound potentials. Improvements in peripheral nerve conduction positively correlated with cytokine‐induced increases in frataxin expression, providing a link between increases in frataxin and neurophysiological function. Abrogation of disease‐related pathology was also evident, with reductions in inflammation/gliosis and increased neural stem cell numbers in areas of tissue injury. Interpretation: These experiments show that cytokines already clinically used in other conditions offer the prospect of a novel, rapidly translatable, disease‐modifying, and neuroprotective treatment for Friedreich's ataxia. Ann Neurol 2017;81:212–226